Genomic Sequence and Phylogenetic analysis of Canine Parvovirus New 2a Variant Strain in Indian Dogs - Vimalan, Yuvachandran Viva; Paramasivam, Raja; Manoharan, Parthiban; Ramalingam, Maha Prabhu; Sivamurthy, Parthiban; Sivamurthy, Parthiban; Gopal, Sathish; Ghadevaru, Sarathchandra (Indian Journal of Veterinary Sciences and Biotechnology, 2023)
In this study, a virulent field canine parvovirus type - 2a variant (CPV-new 2a) strain, ABT/CPV/MVC02, was identified from the faeces of a Dog with severe haemorrhagic gastroenteritis in Chennai, Tamil Nadu, India. The genomic sequence of ABT/CPV/MVC02 (MN661243) shares 99.33% nucleotide identity with those of CPV new 2a variant strains. Based on the VP2 capsid protein amino acid variation (Ser297Ala), the ABT/CPV/MVC02 strain is classified as a new CPV 2a variant strain. Two VP2 mutations Tyr324Ile and Thr440Ala were reported in most of the CPV-2a stains also present in ABT/CPV/MVC02.The phylogenetic analysis of the reported strain revealed that it was distinct from existing CPV 2a strains from India and other countries. This complete genomic analysis revealed that the CPV-2a new variant strain circulating in India is evolving rapidly with unique antigenic variations between field CPV-2a and vaccine strains which may be the major cause for vaccine failure in vaccinated dogs.
Keywords: Canine parvovirus (CPV); CPV-2a Strain; CPV-2b; CPV-2c and Genomic Sequence